2016
DOI: 10.1051/0004-6361/201628950
|View full text |Cite
|
Sign up to set email alerts
|

The missing link: Tracing molecular gas in the outer filament of Centaurus A

Abstract: We report the detection, using observations of the CO(2−1) line performed with the Atacama Pathfinder EXperiment (APEX), of molecular gas in the region of the outer filament of Centaurus A, a complex region known to show various signatures of an interaction between the radio jet, an H i cloud, and ionised gas filaments. We detect CO(2−1) at all observed locations, which were selected to represent regions with very different physical conditions. The H 2 masses of the detections range between 0.2 × 10 6 and 1.1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…Hints that AGN radio lobes may be responsible for heating the atomic/ionized filaments have been reported in several other cluster cores; for example, the high flux of the Fe x coronal line, coincident with the edge of the radio lobe in the Centaurus Cluster (Canning et al 2011), or the unusually strong [O iii] emission at the location where the AGN bubble/jet is interacting with the ionised gas in Abell 3581 (Canning et al 2013). Morganti et al (2016) show that the radio jet in Centaurus A also affects the atomic and ionized to molecular gas ratios, hinting that CO survives the jet-cloud interaction more easily than the other phases, which is opposite to the trend reported here. Below, we speculate on possible scenarios that explain the interaction between the AGN and the molecular gas in M87, and comment briefly on the dynamics of the CO clouds.…”
Section: Discussioncontrasting
confidence: 98%
“…Hints that AGN radio lobes may be responsible for heating the atomic/ionized filaments have been reported in several other cluster cores; for example, the high flux of the Fe x coronal line, coincident with the edge of the radio lobe in the Centaurus Cluster (Canning et al 2011), or the unusually strong [O iii] emission at the location where the AGN bubble/jet is interacting with the ionised gas in Abell 3581 (Canning et al 2013). Morganti et al (2016) show that the radio jet in Centaurus A also affects the atomic and ionized to molecular gas ratios, hinting that CO survives the jet-cloud interaction more easily than the other phases, which is opposite to the trend reported here. Below, we speculate on possible scenarios that explain the interaction between the AGN and the molecular gas in M87, and comment briefly on the dynamics of the CO clouds.…”
Section: Discussioncontrasting
confidence: 98%
“…However, from arguments related to the geometry and kinematics, Neumayer et al (2007) noted that ionized emission such as [Si VI] must indicate an inflow rather than outflow, and it is interpreted as backflow of gas along the side of the jet's cocoon. Also, although farther apart, Salomé et al (2016) and Morganti et al (2016) reported the detection of molecular gas 15 kpc NE from Cen A's centre (i.e. in the region of the outer filament), where there is an ongoing interaction between the radio jet and gas clouds.…”
Section: Comparison With Numerical Simulations Of the Multi-phase Ism...mentioning
confidence: 99%
“…The interaction of cold gas with radio jets has already been studied theoretically and invoked to explain the Hi outflows found in some powerful radio galaxies (Morganti et al 2005;Krause 2007), which have been since augmented by fast molecular gas outflows observed via the traditional method of CO lines (Morganti et al 2015(Morganti et al , 2016. Finally, significant amounts of molecular gas, the fuel of SF, driven out of radio-galaxies via jet-powered outflows provides a natural explanation for the so-called 'alignment effect' observed in many gas-rich high-redshift radio-galaxies (e.g.…”
Section: Radio Galaxies: Molecular Gas and Agn-injected Cosmic Raysmentioning
confidence: 99%